2006
DOI: 10.1093/rpd/nci350
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnostic indicators of renal and bone damage in rats intramuscularly injected with depleted uranium

Abstract: The toxic effects and changes in biochemical markers related to kidney and bone in depleted uranium (DU)-injected rats were examined in order to clarify the relation between clinical biochemical markers and the degree of damage in these organs. Male Wistar rats received a single injection in the femoral muscles of 0.2, 1.0 or 2.0 mg kg(-1) of DU which was dissolved in nitric acid solution adjusted to pH 3.2, for comparison with the group injected with nitric acid solution, and the control group. Urine and faec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
0
16
1
2
Order By: Relevance
“…Plusieurs études ont rapporté une augmentation plasmatique de deux marqueurs communément utilisés mais peu discriminatifs des lésions rénales (la créatinine et l'urée) en cas d'exposition aiguë à l'uranium (par voie intramusculaire ou sous cutanée) (Banday et al, 2008b ;Blantz, 1975 ;Fukuda et al, 2006 ;Gueguen et al, 2006 ;Kobayashi et al, 1984). En parallèle, il a été décrit chez le rongeur, une diminution de la clairance de la créatinine (indicatif d'une diminution du taux de filtration glomérulaire) (Banday et al, 2008b ;Haley, 1982).…”
Section: Physiopathologie (Marqueurs Plasmatiques Et Urinaires)unclassified
See 1 more Smart Citation
“…Plusieurs études ont rapporté une augmentation plasmatique de deux marqueurs communément utilisés mais peu discriminatifs des lésions rénales (la créatinine et l'urée) en cas d'exposition aiguë à l'uranium (par voie intramusculaire ou sous cutanée) (Banday et al, 2008b ;Blantz, 1975 ;Fukuda et al, 2006 ;Gueguen et al, 2006 ;Kobayashi et al, 1984). En parallèle, il a été décrit chez le rongeur, une diminution de la clairance de la créatinine (indicatif d'une diminution du taux de filtration glomérulaire) (Banday et al, 2008b ;Haley, 1982).…”
Section: Physiopathologie (Marqueurs Plasmatiques Et Urinaires)unclassified
“…Conformément à cette atteinte tubulaire, l'augmentation de la concentration urinaire d'enzymes révélatrices de lésions tissulaires (N-acétylglucosaminidase, phosphatase alkaline, gamma glutamyl transpeptidase) a largement été décrite (Banday et al, 2008b ;Diamond et al, 1989 ;Fukuda et al, 2006) ainsi que l'augmentation d'excrétion d'électrolytes, de protéines telles que de béta2-microglobuline qui sont des signes d'altérations tubulaires fonctionnelles (Banday et al, 2008b ;Fukuda et al, 2006 ;Haley, 1982).…”
Section: Physiopathologie (Marqueurs Plasmatiques Et Urinaires)unclassified
“…In Wistar rats, uranium exposure reduced bone growth, volume, and mineralization of the tibial metaphysis (Diaz Sylvester et al, 2002;Fukuda et al, 2006;Guglielmotti et al, 1984;Ubios et al, 1994) and decreased mandibular bone growth (Diaz Sylvester et al, 2002;Pujadas Bigi and Ubios, 2007;Ubios et al, 1994). Similar effects have been reported in the femoral metaphysis of Balb/c mice and the tibial metaphysis of Wistar rats, in which uranium exposure was associated with decreased growth cartilage, bone volume, bone formation surfaces and mineralization (Bozal et al, 2005;Fukuda et al, 2006;Guglielmotti et al, 1984) (see Supplementary Table S1).…”
Section: Uranium-induced Bone Toxicitymentioning
confidence: 99%
“…In Wistar rats, uranium exposure reduced bone growth, volume, and mineralization of the tibial metaphysis (Diaz Sylvester et al, 2002;Fukuda et al, 2006;Guglielmotti et al, 1984;Ubios et al, 1994) and decreased mandibular bone growth (Diaz Sylvester et al, 2002;Pujadas Bigi and Ubios, 2007;Ubios et al, 1994). Similar effects have been reported in the femoral metaphysis of Balb/c mice and the tibial metaphysis of Wistar rats, in which uranium exposure was associated with decreased growth cartilage, bone volume, bone formation surfaces and mineralization (Bozal et al, 2005;Fukuda et al, 2006;Guglielmotti et al, 1984) (see Supplementary Table S1). Cabrini et al (1984), Guglielmotti et al (1984Guglielmotti et al ( , 1985Guglielmotti et al ( , 1987, and Ubios et al (1991) observed that acute uranium exposure resulted in decreased osteoblast activity and intramembranous ossification in Wistar rats (Table 1) Guglielmotti et al, 1985Guglielmotti et al, , 1984Ubios et al, 1990).…”
Section: Uranium-induced Bone Toxicitymentioning
confidence: 99%
See 1 more Smart Citation